Experimental Measurements of Dynamic Bulk Modulus of Oil - Adam BUREČEK; Lumír HRUŽÍK (Transactions of the VŠB-Technical University of Ostrava, Mechanical Series, 2012)
The experimental measurement and evaluation of the dynamic bulk modulus of hydraulic oil is the object of the paper. We take into account the dynamic bulk modulus during the fast processes taking place in the order of several tens milliseconds. The measurement is done using experimental equipment to measure pressure difference depending on time.